The effect of NQO1 polymorphism on the inflammatory response in cardiopulmonary bypass - İSBİR, CEMİL SELİM; ARSAN, SİNAN (WILEY, 2008)
Cardiopulmonary bypass (CPB) has been associated with systemic inflammatory response syndrome (SIRS). Endothelial dysfunction related to non-laminar flow during CPB is known to play a key role in this complex pathology. Antioxidant response element (ARE) dependent NAD(P)H:quinone oxidoreductase 1 (NQO1) promoter is a regulatory element involved in the anti-inflammatory mechanism in vasculature exposed to non-laminar flow. Mutation of the NQO1 could represent a novel anti-inflammatory effect in CPB. The goal of this study was to demonstrate whether genetic variants of NQO1 affect cytokine release after CPB. Eighteen patients who underwent standard coronary artery bypass grafting (CABG) operation were included in the study. Genotyping for NQO1 was performed. Serum Interleukin-6 (IL-6) levels were measured before induction, during CPB after declamping the aorta, and 24 h after operation. Clinical data were collected respectively. Seven patients were NQO1 T carriers and 11 patients were NQO1 T non-carriers. During CPB, IL-6 concentrations were increased in NQO1 T carriers compared to T non-carriers (p = 0.038). Although ventilation times and blood loss were higher in T carriers these were not statistically significant. Patients with NQO1 T carriers showed significantly higher IL-6 levels during CPB. Non-laminar flow during CPB may diminish the transcriptional activation of the NQO1 in T carriers. Preoperative determination of this novel anti-inflammatory mechanism could be useful to improve operative outcome in CPB. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: inflammation; cardiopulmonary bypass; NQO1; PCR-RFLP; GENETIC POLYMORPHISMS; ENDOTHELIAL-CELLS; OXIDATIVE STRESS; LAMINAR; RISK